The Sociopolitical Changes and the Foreign Language Planning and Policy in KRI: The Case of English Language - Momen Yaseen M., Amin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The current thesis presents a detailed study on language planning and policy in the Kurdistan Region of Iraq (KRI) vis-à-vis the role of English. The topic is formulated under the framework of social action theory which infers that each ethnic group strives to be represented in terms of language rights and standardization and, as a result, language becomes a domain where groups contend to assert their power. The research pursues a mix-method design to consider the linguistic landscape from different perspectives, including a critical socio-historical approach. Considering the sociopolitical developments, both top-down and bottom-up approaches in planning language policy were adopted. The questionnaires were used to analyse the Kurdish students’ responses towards using English as a medium of instruction. Besides, the attitudes of Kurdish parents of the region were also recorded in the study. Further, the correlation analysis reveals that Kurdish parents hold positive attitudes; however, they have been influenced by religious and national factors. It has been revealed that Kurdish parents confer more importance on studies in Kurdish or religion than on English language education. The major argument in this thesis aims to overview a reliable or valid image of linguistic landscape and presents a transformative language planning and policy to Kurdish authorities, as an alternative to the current situation of LL. The transformative language planning and policy, which promotes pertinent guidelines to reform and redesign the language planning and policy, can be congenial for planning a new language policy to this region. The critical analysis of relevant documents to language planning and policy reveals that there is an unsystematic framework of linguistic landscape in the region, and the efforts couldn’t meet the expectations of changing socio-economic episodes of the region.

ÖZ: Yapılan tez çalışmasında, Irak Kurdistan Bölgesi’ndeki (KRI) dil planlaması ve dil politikası hakkında ayrıntılı bir çalışma sunulmaktadır. Bu tezin ileriki bölümlerinde 1991 yılında Kuzey Irak Bölgesel Kürt Yönetimine geri verilen coğrafyadaki dil planlamasına -ki bu planlama örtük olarak yapılmıştır-irdeleyici bir biçimde ele alınacaktır. Tez çalışması Sosyal Eylem Kuramını temel almış ve çalışmayı bu kuramından hareketle oluşturulmuştur. Bu bakımdan tez çalışmasında dil planlaması ve politikaları, özellikle İngilizce eğitiminin geçirmiş ve geçirmekte olduğu kimi gelişmeler ışığında incelenmesi gerçekleştirilmiştir. Tez çalışmasının araştırma deseni Karma Yöntem ile kurgulanmış, DilselGörünümleri farklı bakış açılarından ve irdeleyici Tarihsel Toplumdilbilim yaklaşımı ile gerçekleştirilmiştir. Çalışmada bölgedeki dil planlamasına yönelik belgeler, anayasal, hükümet, meclis yanında siyasi partiler ve basın bağlamında incelenmiştir. Araştırmacı çalışmasında güncel bağlamdaki dil politikaları üzerine yoğunlaşmıştır. Çalışmada bürokratik ve bürokratik olmayan, anayasallaşma, resmileşme, ölçünleşme ve yasama bağlamında bağımsız olmayan bir devletin, dil siyasalarını incelemiş, ve yapılan dil planlamalarının herhangi bir sistem odağına sahip olmadığını saptamıştır. Çalışmada Kürt ortaokul öğrencilerinin İngilizce eğitiminin olumlu ve olumsuz yanlarına yönelik davranışsal, zihinsel ve duygusal durumlarını öğrenmek için sormaca uygulanmıştır. Yapılan değerlendirmelerde Kürt öğrencilerin İngilizce eğitimine yönelik olumlu tutum sergiledikleri belirlenmiştir. Bunun yanında, eşdeşleme (correlation) çalışması sonucunda öğrenci velilerinin İngilizce’ye yönelik olumlu tutumları olmasına karşın, dini ve ulusalcılık/ulusculuk bağlamında ciddi etki altında oldukları da belirlenmiştir. Elde edilen sonuçlar doğrultusunda öğrenci aileleri, İngilizce eğitimi yerine Kürtçe’ye büyük önem verdikleri ve Kürtçe ile din bağlamında çalışılmasının büyük anlam ifade ettiği vurgulanmıştır. Bu çalışmadaki temel amaç geçerli ve güvenilir bir dilsel görünümün yapılması yanında, Kürt yetkililere dönüşümsel dil planlaması ve siyasalarını dil eğitimi bağlamında ortaya kayabilmektir. Dönüşümsel dil planlamasının yenilikçi ve yeniden tasarlayıcılık gibi bir dizi aşaması bulunduğu bilinmektedir. Tam da bu bakımdan, dönüşümsel dil planlaması söz konusu coğrafyada yeni bir dil planlaması için uyumlaştırıcı bir rol oynayacağı düşünüşmektedir.
Master of Arts in English Language Teaching (ELT). Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Education, Dept. of Foreign Language Education, 2022. Supervisor: Assoc. Prof. Dr. Javanshir Shibliyev.
Keywords: Thesis Tez; English Language Teaching (ELT) Department; English Language Teachers--English Study and Teaching--Online Teaching; Covid 19 Pandemic--English Teaching--Online Teaching; Emergency Remote Teaching; Online Language Teaching; Distance Education; English Preparatory School; English Language; ICT; Embedded Sing-case Study; Snowball Sampling; Mixed Methods Research; Covid-19; Pandemic